An investigation on reorientation and textural evolution in a martensitic NiTi rolled sheet using EBSD. (December 2022) - Xiao, J.F.; Cayron, C.; Logé, R.E.
Highlights: Variant reorientations and textural evolution in the martensitic NiTi sheet were systematically investigated using Electron Backscatter Diffraction (EBSD) technique. Two models based on the interaction work were employed to better understand the variant reorientations within parent B2 grains during deformation, (PTMC and newly developed Correspondence Theory (CT)). It shows that the CT method works better than the PTMC. The dependences of formation of single-variant and bi-variants blocks of martensite and evolution of textures on initial microstructures were theoretically explored using CT method as well as the simulations. An excellent agreement with the EBSD experiments can be achieved. In addition, based on the results, a modified criterion of interaction work for variant reorientations was proposed. The NiTi alloys with various initial microstructures were further simulated based on the CT method as well as the modified criterion, during which the good agreements with experimental reports were found. Abstract: Variant reorientation is a ubiquitous phenomenon in shape memory alloys and has a great influence on their texture and mechanical response. In the present study, a martensitic NiTi rolled sheet is investigated by the electron backscattering diffraction (EBSD) technique; the variant reorientation and texture evolution are followed during bending. The initial weak texture components of martensite evolve by reorientation toward a strong texture around [ 1 ¯ 04 ]M and a weak one around [ 1 ¯ 12 ]M . The initial laths are transformed into blocks made of one or two variants. The EBSD maps were analyzed with the Interaction Work (IW) criterion associated with (a) the individual variant and (b) habit plane variants (a combination of two distortion variants). Compared with the experimental results, the prediction given with individual variant fits better than with the habit plane variants. An empirical quantification of the threshold on interaction work (IW) permits to rationalize and predict the variant pairs formed by the reorientation and their numbers in the blocks. A critical influence of the pre-texture of the parent B2 grains on the final texture and on the number of variants per block was revealed. This study could give insights into the mechanical response of the NiTi alloys with various textures during tensile and fatigue tests. Graphical abstract: Image, graphical abstract